2020
DOI: 10.3390/jof6040189
|View full text |Cite
|
Sign up to set email alerts
|

Application of Probiotic Yeasts on Candida Species Associated Infection

Abstract: Superficial and life-threatening invasive Candida infections are a major clinical challenge in hospitalized and immuno-compromised patients. Emerging drug-resistance among Candida species is exacerbated by the limited availability of antifungals and their associated side-effects. In the current review, we discuss the application of probiotic yeasts as a potential alternative/ combination therapy against Candida infections. Preclinical studies have identified several probiotic yeasts that effectively inhibit vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 79 publications
(104 reference statements)
0
19
0
4
Order By: Relevance
“…Another alternative method that has successfully passed preclinical and clinical trials in the case of C. albicans infection is the use of yeast-based probiotics [313][314][315][316]. It has been shown that Saccharomyces boulardi secreted into the medium active compounds, such as caproic acid, which reduce the virulence of C. albicans mainly by inhibiting the production of hyphae [314].…”
Section: Alternative Methods Formentioning
confidence: 99%
See 2 more Smart Citations
“…Another alternative method that has successfully passed preclinical and clinical trials in the case of C. albicans infection is the use of yeast-based probiotics [313][314][315][316]. It has been shown that Saccharomyces boulardi secreted into the medium active compounds, such as caproic acid, which reduce the virulence of C. albicans mainly by inhibiting the production of hyphae [314].…”
Section: Alternative Methods Formentioning
confidence: 99%
“…It has been shown that Saccharomyces boulardi secreted into the medium active compounds, such as caproic acid, which reduce the virulence of C. albicans mainly by inhibiting the production of hyphae [314]. Also, in the case of other Candida species, it has been shown that two strains of probiotic yeast-Saccharomyces cerevisiae and Issatchenkia occidentalis-were shown to be able to inhibit adhesion to both abiotic surfaces and epithelial cells, inhibit morphological changes and biofilm formation, i.e., not only by C. tropicalis and C. auris species but also by mixed biofilms coproduced with C. albicans [315,316]. Interestingly, the action of S. cerevisiae and I. occidentalis was more potent than that of S. boulardi, which best inhibited the biofilm of C. albicans [314][315][316].…”
Section: Alternative Methods Formentioning
confidence: 99%
See 1 more Smart Citation
“…The only probiotic yeast commercially available is S. cerevisiae var . boulardii , aggregated to pathogens and able reduce their virulence through inhibiting the adhesion and morphological transition of Candida spp., and could be promising therapeutic options [ 106 ].…”
Section: Combination Therapies and Novel Treatmentsmentioning
confidence: 99%
“…This work summarizes the participation of S. boulardii in these mechanisms and the multifactorial nature by which this yeast modulates the host microbiome and intestinal function. The second paper assigned to probiotics, written by Kunyeit et al [ 19 ], summarize how probiotic yeasts can be applied against Candida species associated infections. Superficial and life-threatening invasive Candida infections are a major clinical challenge in hospitalized and immuno-compromised patients.…”
mentioning
confidence: 99%